The Development of Problem-Based Learning Students Liveworksheets on Three Variables Linear Equation System - Meli Hendriani; Euis Eti Rohaeti; Nelly Fitriani ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Problem-solving ability is important for students to possess because life is inseparable from problems. However, in reality, students' problem-solving ability, especially in mathematics learning, remains relatively low, including in the Three Variable Linear Equation System (SPLTV) material. This study aims to validate the problem-based learning student worksheet, assisted by liveworksheets, for the SPLTV material as an alternative teaching material to improve students' mathematical problem-solving ability. The research method used a Development Study research design, involving four material experts and two media experts in the validation process. The research instrument used questionnaires for validation and a one-to-one interview instrument with three grade X MA students. Data analysis was carried out using descriptive statistical techniques to calculate the average percentage of the validation results. The validation results showed that the worksheet prototype was categorized as very valid with a score of 86.14%, and the learning media was categorized as very valid with a validity score of 91.67%. The interview results with three students indicated that the worksheet was feasible and practical to use. Based on the research results, the problem-based learning worksheet, assisted by Liveworksheets, met the validity standards; therefore, it is feasible to test after revisions based on the validators' suggestions.